Desain Pembelajaran Pendidikan Agama Islam Berbasis Masalah untuk Mengembangkan Nilai-nilai Karakter Religius - Lilik Nur Kholidah (Journal on Education, 2024)
Developing religious character values is an important aspect in the learning objectives of Islamic education. This effort is a response to problems in learning Islamic education which is still conventional. A literature study approach is used to collect data sources from scientific literature. The research findings show that the design for developing religious character values in learning problem-based Islamic education courses, including thoughts, concepts and activities, transforms humanist Islamic religious character values in the learning subjects. This safe problem-based learning design is also a response to the challenges of religious character education, which in its management practice has not departed from the theory, concept, design of Islamic teaching values so as to achieve a transformation of the learner's religious character. This design for developing religious character values in problem-based Islamic religious education learning is a form of theoretical concept formulation of the function of learning design as a learning design activity to achieve the goals of Islamic education in developing the religious character of learners.